Lesson Learned about the Public Health Emergency Management: a Case Study of the Outbreak of COVID-19 in Chonburi Province - กตัญญุตานนท์ อภิรัต (Journal of Health Science of Thailand, 2023)
This qualitative research aimed to draw lessons learned about public health emergency management in the outbreak of COVID-19 in Chonburi province, a province in the Eastern Economic Corridor project of Thailand. Concept of six building block of health system and public health emergency management cycle (2P2R - prevention, preparedness, response, and recovery) were applied. Data collection began in January 2020 and completed in September 2022 by using in-depth interviewing and focus group discussion method. The data were analyzed with a content and thematic analysis. It was found that (1) Chonburi Communicable Disease Committee showed the leadership in concrete management with the health information; (2) manpower in both of health sector and non-health sector had empowered the procedure of operation through on-the-job training and continuous coaching method by the committee and health experts; (3) budget, medical supplies, medications and vaccine were sought and allocated from the government and local government organizations in this area; (4) health information system collaborated through a cooperation network among the government sector, private sector, and civil society at both provincial and local levels; (5) health finance operated according to the budget allocation in accordance with its mission; and (6) health services were provided in accordance with the measure of public health emergencies management. The local units of communicable disease prevention and control were advised to be well-prepared in pre-evidence, investigate and search for patients during incident and continuously communicate risk to the public. The measures to relieve the situation for education establishments, organizations and restaurants were determined for the post-pandemic. According to the lessons learned, there are several challenge areas in term of disease control decisions coupled with the economy, risk communication in managing crisis situations. Therefore, there are recommendations regarding preparedness for the risk groups in quarantine areas, risk communication with the public, and resource management planning for new emerging infectious diseases in a collaborative manner involving all sectors including the business sector, to be prepared for disease surveillance, prevention, and control for next pandemic.